If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 3y + 6z = 42 Solving 5x + 3y + 6z = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 5x + 3y + -3y + 6z = 42 + -3y Combine like terms: 3y + -3y = 0 5x + 0 + 6z = 42 + -3y 5x + 6z = 42 + -3y Add '-6z' to each side of the equation. 5x + 6z + -6z = 42 + -3y + -6z Combine like terms: 6z + -6z = 0 5x + 0 = 42 + -3y + -6z 5x = 42 + -3y + -6z Divide each side by '5'. x = 8.4 + -0.6y + -1.2z Simplifying x = 8.4 + -0.6y + -1.2z
| y=0.05(x-30)+6 | | 0.2x+6=1.2x | | y=0.05(x-30)2+6 | | 6x+2y+4z=36 | | 2^3(x-3/4)-12=2 | | -10v^2-4p^2+5h^2= | | 5p-3(p-5)+4(q-5)= | | 3(2a-8)=4(7+a) | | 2x+4y+2z=30 | | (5-2x)/(4x-10) | | 10a-20=6a+4 | | 7+66x=-33+16 | | x^2+41=y^2 | | 15x=-22 | | x*x-12=78 | | y=-120x+1500 | | 3x-10y=-164 | | n^2-(1-k)n=40 | | 8x-42=-2 | | x+79+36=180 | | 1+n+4=9 | | X+7.64=25 | | 423x=89-3 | | 7(3.14x)= | | 7pieX= | | x^2+y^2-4y=1 | | -(-8-4)=a | | 10-2=8-3x | | -2y+16=20 | | 4b-4=2b+14 | | -0.084x^2+0.839x+5=0 | | 6(3+2a)=42 |